Analisis Kemampuan Motorik Ditinjau dari Perbedaan Pola Bermain pada Anak Usia 12-15 tahun - Armada Yusuf Fadillah; Nanik Indahwati (MAN Insan Cendekia Jambi, 2026)
The development of motor skills in early adolescence is crucial for supporting physical activity and health. However, play patterns are increasingly shifting toward technology use, potentially affecting movement quality. This study aims to analyze differences in motor skills based on play patterns and to evaluate the relationship between play patterns and motor skills. This research employed a quantitative method with a comparative descriptive design involving 90 adolescent samples selected via purposive sampling from a population of 211 students at SMP Labschool Unesa. Data were collected using motor tests and questionnaires. The Kruskal-Wallis test results (0.153) indicated no significant difference in motor skills based on play patterns. Meanwhile, the Eta test results with play patterns as the dependent variable (η = 0.991) and total motor skills as the dependent variable (η = 0.221) demonstrated that motor skills have a weak relationship with play patterns, whereas play patterns serve as a strong predictor for motor skills. The study concludes that while play patterns do not yield significant differences in motor skill levels, a balance of play activities remains necessary to support adolescent motor development.